PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 1 DUA KOTO PASAMAN - Yulianti Rasyid, Dianni Novalia, Yasnur Asri, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The aim of this study to described the effect of the use of problem-based learning model to the skills of writing news class VIII students SMP Negeri 1 Dua Koto. This research type was quantitative research with experiment method. The design of this research was one group pretest and posttest design. Instrument used in this research is performance test. Based on the results of research using problem based learning model (PBL), proved itâ€™s have an effect on writing skill of class VIII students of SMP Negeri 1 Dua Koto.Â Kata Kunci: pengaruh, model problem based learning, menulis berita